(untitled) (Journal of Pathology of Nepal, 2022)
Background: Urinary tract cytology is an accurate test for the detection of urothelial malignancy especially high-grade urothelial carcinoma. The Paris System for Reporting Urinary Cytology was introduced to standardize urinary tract cytology reporting. We aim to evaluate the utility of reporting urinary cytology as per this system and correlate with histopathology. Materials and Methods: This is a descriptive cross-sectional prospective study conducted on urine samples submitted for cytological examination at Kathmandu Medical College Teaching Hospital, Sinamangal, Nepal between 1st November 2020 to 31st July 2021. Ethical consent was taken from the Institutional Review Committee. Urine cytology was reported as per The Paris System for Reporting Urinary Cytology and correlated with the histopathologic diagnosis. Sensitivity, specificity, positive predictive value, and negative predictive value were calculated for the high-grade and low-grade urothelial lesion. Results: A total of 104 urine samples were evaluated. Biopsy specimens were available for 38 cases. Urine cytology consisted of 1.92% non-diagnostic cases, 69.23% negative for high-grade urothelial carcinoma, 5.76% atypical urothelial cells, 5.76% suspicious for high-grade urothelial carcinoma, 13.46% high-grade urothelial carcinoma, and 3.84% low-grade urothelial neoplasm respectively. Sensitivity, specificity, negative predictive value and positive predictive value were 90.48%, 82.35%, 86.37% and 87.5% respectively for high grade urothelial carcinoma and 40%, 93.9%,50% and 91.17% respectively for low grade urothelial lesions. Conclusions: Our study shows that reporting urine cytology as per The Paris System for Reporting Urinary Cytology provides high sensitivity for the detection of high-grade urothelial lesions.